Physiological and morphological responses to feeding in broad-nosed caiman (Caiman latirostris) - Starck, J. Matthias; Cruz-Neto, Ariovaldo P.; Abe, Augusto Shinya (Company of Biologists Ltd, 2007)
Broad nosed caiman are ectotherm sauropsids that naturally experience long fasting intervals. We have studied the postprandial responses by measuring oxygen consumption using respirometry, the size changes of the duodenum, the distal small intestine, and the liver, using repeated non-invasive ultrasonography, and by investigating structural changes on the level of tissues and cells by using light- and electron microscopy. The caimans showed the same rapid and reversible changes of organ size and identical histological features, down to the ultrastructure level, as previously described for other ectothermic sauropsids. We found a configuration change of the mucosa epithelium from pseudostratified during fasting to single layered during digestion, in association with hypertrophy of enterocytes by loading them with lipid droplets. Similar patterns were also found for the hepatocytes of the liver. By placing the results of our study in comparative relationship and by utilizing the phylogenetic bracket of crocodiles, birds and squamates, we suggest that the observed features are plesiomorphic characters of sauropsids. By extending the comparison to anurans, we suggest that morphological and physiological adjustments to feeding and fasting described here may have been a character of early tetrapods. In conclusion, we suggest that the ability to tolerate long fasting intervals and then swallow a single large meal as described for many sit-an-wait foraging sauropsids is a functional feature that was already present in ancestral tetrapods.
Keywords: specific dynamic action; postprandial; metabolism; gastrointestinal tract; crocodiles; ultrasonography